Layered Birnessite Cathode with a Displacement/Intercalation Mechanism for High-Performance Aqueous Zinc-Ion Batteries - Xian-Zhi Zhai; Jin Qu; Shu-Meng Hao; Ya-Qiong Jing; Wei Chang; Juan Wang; Wei Li; Yasmine Abdelkrim; Hongfu Yuan; Zhong-Zhen Yu (Nano-Micro Letters, 2020)
Abstract Mn-based rechargeable aqueous zinc-ion batteries (ZIBs) are highly promising because of their high operating voltages, attractive energy densities, and eco-friendliness. However, the electrochemical performances of Mn-based cathodes usually suffer from their serious structure transformation upon charge/discharge cycling. Herein, we report a layered sodium-ion/crystal water co-intercalated Birnessite cathode with the formula of Na0.55Mn2O4·0.57H2O (NMOH) for high-performance aqueous ZIBs. A displacement/intercalation electrochemical mechanism was confirmed in the Mn-based cathode for the first time. Na+ and crystal water enlarge the interlayer distance to enhance the insertion of Zn2+, and some sodium ions are replaced with Zn2+ in the first cycle to further stabilize the layered structure for subsequent reversible Zn2+/H+ insertion/extraction, resulting in exceptional specific capacities and satisfactory structural stabilities. Additionally, a pseudo-capacitance derived from the surface-adsorbed Na+ also contributes to the electrochemical performances. The NMOH cathode not only delivers high reversible capacities of 389.8 and 87.1 mA h g−1 at current densities of 200 and 1500 mA g−1, respectively, but also maintains a good long-cycling performance of 201.6 mA h g−1 at a high current density of 500 mA g−1 after 400 cycles, which makes the NMOH cathode competitive for practical applications.